PEMROGRAMAN MOTOR STEPPER DENGAN MENGGUNAKAN BAHASA PEMROGRAMAN C - Kalatiku, Protus Pieter; Joefrie, Yuri Yudhaswana (MEKTEK, 2011)
This journal delivers topic about basic programming of stepper motor using C language. Its scoope isstepper motor construction of bipolar and unipolar, controlling type (half step and full step) and the use of Clanguage to operate stepper motor. CodeVisionAVR combined with library of AVR Studio4 is used as editorand compiler